Precision intervention for prostate cancer: Re-evaluating who is at risk. (10th July 2022) - Papachristodoulou, Alexandros; Abate-Shen, Cory
Abstract: The vast majority of new prostate cancer diagnoses are low-grade tumors that are monitored by active surveillance rather than undergoing immediate treatment. However, a subset of men will progress to advanced prostate cancer which may result in lethality, and these men are likely to benefit from early intervention to prevent or delay such progression. For this high-risk group, which includes aged men, men of African descent, and those with a hereditary predisposition to prostate cancer, informed risk stratification can be the cornerstone of clinical decision making and treatment intervention. In this review, we discuss the importance of a precision intervention approach that considers the cumulative risk for a given patient or population to develop prostate cancer or to progress to lethal disease, with particular focus on the interplay of major determinants of high-risk disease. Highlights: Age, race, oxidative stress and inflammation influence prostate cancer risk. Genetic factors play a pivotal role in predicting prostate cancer onset and outcome. Nuclear and mitochondrial genetic alterations point to prostate cancer susceptibility. Integrative risk assessment may improve precision prostate cancer intervention.